Photochemistry of Three Selected Pharmaceuticals in Seawater and River Water - SAVCI, Serpil (International Journal of Natural Sciences Research, 2015)
The aim of these work was to study the direct photolysis of three pharmaceuticals with relatively high potential ecological risk and high consumption-namely, fluconazole, bicalutamide and anastozole promoted by photochemical processes. By conducting experiments in Milli Q water, Baltic Sea Water and Olandsån River Water. To evaluated this process under laboratory conditions, used chemical actinometer for sunlight measurements. The actinometer is the known bicalutamide, fluconazole and anastozole the half life in sunlight ranging from several minutes to 120 minutes. The systems were relatively persistent against sunlight. It has quantum yield invariant with wavelength to 261 nm for fluconazole 271 nm for bicalutamide and 269 for anastozole.